Current market situation and prospects of the Ukrainian and world egg market - Krulikovska, Natalia (My University, 2014)
Chicken egg is one of the cheap and therefore available source of protein in the human diet. Before industrialization of the agricultural sector the production of eggs was focused exclusively on local markets. However, from the middle of the last century egg business became global.
Keywords: agricultural sector; business; chicken egg; сільськогосподарський сектор; бізнес; куряче яйце; agricultural sector; business; chicken egg